1999
DOI: 10.1021/ja992668n
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Synthesis of Peptide C-Terminal Thioesters by Fmoc/t-Bu Chemistry

Abstract: Peptide C-terminal thioesters are key intermediates in a variety of applications, most notably the recently developed native chemical ligation methods for the total chemical synthesis of proteins. So far they have been prepared only by the use of the least prevalent Boc/benzyl solid-phase method on ad hoc prepared resin supports. We describe here a novel method for the solid phase synthesis of thioesters by the most prevalent Fmoc/t-Bu method. The method is based on the use of a 3-carboxypropanesulfonamide saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
173
1
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(185 citation statements)
references
References 42 publications
0
173
1
11
Order By: Relevance
“…The need to make large numbers of analogs of thousands of native proteins by chemical ligation, and hence to prepare many tens-of-thousands of peptide segments, provides an unprecedented impetus for the development of efficient methods of peptide synthesis. We can look forward with confidence to the development of radically improved methods for the rapid, costeffective preparation of large numbers of unprotected peptide-thioester segments for use in chemical protein synthesis (124).…”
Section: Chemical Synthesis Of Peptide Segmentsmentioning
confidence: 99%
“…The need to make large numbers of analogs of thousands of native proteins by chemical ligation, and hence to prepare many tens-of-thousands of peptide segments, provides an unprecedented impetus for the development of efficient methods of peptide synthesis. We can look forward with confidence to the development of radically improved methods for the rapid, costeffective preparation of large numbers of unprotected peptide-thioester segments for use in chemical protein synthesis (124).…”
Section: Chemical Synthesis Of Peptide Segmentsmentioning
confidence: 99%
“…This method uses an intramolecular native chemical ligation [57], in which the peptide sequence contains an N-terminal cysteine and an α-thioester group at the C-terminus [58][59][60]. Both tert-butyloxyxarbonyl (Boc)-and 9-fluorenyloxycarbonyl (Fmoc)-based chemistries have been used to incorporate C-terminal thioesters during chain assembly (Boc) [61][62][63] or using a safety-catch based linkers (Fmoc) [60,[64][65][66][67]. Once the peptide is cleaved from the resin, both cyclization and folding are carried out in a single pot reaction.…”
Section: Chemical Synthesis Of Cyclotidesmentioning
confidence: 99%
“…Ingenito et al [45] and Shin et al [24] independently reported in 1999 the Fmoc-based SPPS of C-terminal thioesters using Kenner's acyl-sulfonamide safety catch linker [46] as modified by Backes et al [47,48]. This acyl-sulfonamide linker is completely stable to basic or strongly nucleophilic conditions and can be activated by treatment with either trimethylsilyldiazomethane (TMS-CHN 2 ) or iodoacetonitrile to provide a N-alkyl acylsulfonamide, which is susceptible to nucleophilic attack.…”
Section: Solidmentioning
confidence: 99%
“…This acyl-sulfonamide linker is completely stable to basic or strongly nucleophilic conditions and can be activated by treatment with either trimethylsilyldiazomethane (TMS-CHN 2 ) or iodoacetonitrile to provide a N-alkyl acylsulfonamide, which is susceptible to nucleophilic attack. Activation with TMS-CHN 2 gives usually better thiolysis yields [45]. The synthetic scheme to obtain peptide thioesters through this approach is illustrated in Scheme 2.…”
Section: Solidmentioning
confidence: 99%